Circulating miRNAs: cell–cell communication function? - Turchinovich, Andrey; Samatov, Timur R.; Tonevitsky, Alexander G.; Burwinkel, Barbara (Frontiers in Genetics, 2013)
Nuclease resistant extracellular miRNAs have been found in all known biological fluids. The biological function of extracellular miRNAs remains questionable; however, strong evidence suggests that these miRNAs can be more than just byproducts of cellular activity. Some extracellular miRNA species might carry cell-cell signaling function during various physiological and pathological processes. In this review, we discuss the state-of-the-art in the field of intercellular miRNA transport and highlight current theories regarding the origin and the biological function of extracellular miRNAs.